COMPARATIVE EVALUATION OF PRESSURE DISTRIBUTION BETWEEN HORIZONTAL AND VERTICAL WELLS IN A RESERVOIR (EDGE WATER DRIVE) (Nigerian Journal of Technology, 2017)
This paper presents comparative analysis between the pressure behavior of a horizontal well and a vertical well both subject to edge water drive. Green and source function were used to evaluate the performance of horizontal well and vertical well, eventually, compared based dimensionless pressures and pressure derivatives computed by varying the reservoir geometry. Results presented as type curves show that the rate of decline of the pressure derivative curve is more sharper and sensitive in vertical well than horizontal well of the same geometry indicating a shorter period of clean oil production in vertical well than the horizontal well. The period of radial flow as shown by the horizontal flattened part of the type curve indicate that for all reservoir geometry, the horizontal well will be able to sustain longer period of the radial flow than vertical well given infinite conductivity condition.http://dx.doi.org/10.4314/njt.v36i2.19